INFLECTIONAL MORPHEMES IN THE LYRICS OF THE CALUM SCOTT’S SONGS IN THE ALBUM, BRIDGES - Kusumawardhani, Paramita; Sihombing, Eklesia (JOURNAL OF LANGUAGE, 2024)
Inflectional morphology is part of morphology which is the smallest significant unit of grammar. Morphology itself means the study of morphemes which are the smallest significant units of grammar. There are two parts in morphology here are: derivational morphology which is related to affixes such as suffixes, infixes, prefixes, ablaut and reduplication, meanwhile inflectional morphology which is related to plural, possessive, past time, progressive, and comparative and superlative. There are two kinds of morpheme; they are free morpheme and bound morpheme. Morpheme that can stand on their own are called free, and ones that cannot are bound. This research focused on inflectional morpheme in the lyrics of the Calum Scott’s Songs in the album Bridges. The lyrics in the album Bridges were used as the data of the research. Qualitative method was used as the method and the results were some inflectional morphemes found in the lyrics of the Calum Scott’s Songs in the album Bridges.